Long-term trends and fine year-to-year tuning of phytoplankton in large lakes are ruled by eutrophication and atmospheric modes of variability - Salmaso, Nico; Cerasino, Leonardo (Hydrobiologia, 2012)
This study demonstrated how the impact of eutrophication in a deep lake at the southern border of the Alps (Lake Garda) was finely regulated by specific modes of atmospheric circulation relevant for the Mediterranean area. In the lake district south of the Alps eutrophication still represents the main source of human impact. At the decadal scale the interannual fluctuations of nutrients and phytoplankton growth in Lake Garda were strictly controlled by the long term eutrophication history which characterised the lake since the 1970s. At the annual scale, year-to-year fluctuations in nutrients and phytoplankton were controlled through a chain of causal factors centred on deeply penetrative mixing events determining an upward transport of phosphorus from the hypolimnion to the trophogenic layers. The extent of mixing was in turn controlled by lake and air winter temperature, which were ultimately regulated by the fluctuations of the East Atlantic (EA) pattern from December through February. In its negative state the EA shows an intense high pressure over the West Atlantic, causing a north-easterly airflow bringing cold air from continental Europe to Mediterranean, thus favouring greater lake mixing and nutrient fertilisation. This process is attenuated with a change of the EA towards positive values. Cyanobacteria (mostly Planktothrix rubescens) were the organisms which greatly benefitted from the long-term increase in phosphorus concentrations and the year-to-year fluctuations in surface phosphorus availability controlled by the EA. Given the same availability of phosphorus in the water column, positive winter EA phases weakened the eutrophication effects and phytoplankton development